Prevalence and Practice of Self-Medication among Female - Gutierrez, Jesusa V.; Al-Balawi, Rawan; Al-Anazi, Ghadah; Al-Rashidi, Bashayer; Al-Homaidi, Manal; Al-Atawi, Shemah; Al-Harfy, Maryam (European Scientific Journal, ESJ, 2020)
Background: Self-medication is a prevalent practice among undergraduate nursing students in Saudi Arabia. This undertakes a great significance among nursing students as they are going to be future healthcare practitioners. Purpose: To determine the prevalence and practices of selfmedication among the female nursing students of the University of Tabuk. Methods: A cross-sectional descriptive design using a pre-constructed questionnaire. The respondents were 128 currently enrolled female nursing students through census sampling. Ethical considerations were done in the conduct of the study. Results: The findings revealed a high prevalence of selfmedication with 79.7%. Most of the respondents were 19 years old (27.3%), second and the fourth year, 66 (51.6%) with family income of >8000 SAR per month, 84 (65.6%). Top reason for self-medication is to save time (51%) for the top three upper body diseases such as headache (76.6%), runny nose (37.3%) and dental pain (37.3%); for body diseases were nausea (16.7%) and fever (16.7%) and for Lower body diseases were wounds (25.5%). The commonly used medicines were Analgesic (90.2%), skin ointment (40.2%), cough syrup (23.5%) and the traditional medicines (62%). Brands selection depended on old prescription (37.3%). The main factor for the selection of the drug was the type of traditional (60.8%) due to price and pharmaceutical company. Such medicines for self-medication were obtained from pharmacy shop 89 (87.3.5%) where half (51%) of the respondents read prescription information before self-medicating. Finally, no association was found between the profile and prevalence of self-medication. Self-care is necessary but must be carried out in a safe and responsible actions of self-medicating. Recommendation: The Saudi government must bolster its laws and policies governing Food and drug administration. Though the participants are nursing students, they must be educated with a great emphasis on safe medications and be aware of the side effects, especially those who are not taking pharmacology subject yet as part of the Nursing course.